THE EFFECT OF DIVIDEND POLICY, SALES GROWTH AND ASSET GROWTH ON COMPANY VALUE WITH MEDIA EXPOSURE AS A MODERATION VARIABLE - Indah Umiyati; Trisandi Eka Putri; Wellcy Zahratunijah Az-Zahra (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2024)
Company value is the selling value of an ongoing company. The company value is indicated by the stock price. It can be assumed that the factors that can affect the value of the company include dividend policy, sales growth and asset growth as well as media exposure as a moderating variable. The population in this study are energy sector companies listed on the Indonesia Stock Exchange in 2017-2021. This type of research is quantitative research. With the sampling method purposive sampling. 66 companies were obtained from a total of 69 companies with 5 years of observation, so that 100 data were obtained for analysis according to the research criteria. The data analysis technique used in this study uses multiple regression analysis and Moderating Regression Analysis (MRA). The results showed that the dividend policy variable had a positive effect on firm value, sales growth had no effect on firm value, asset growth had no effect on firm value, besides that media exposure was not able to moderate the effect of dividend policy on firm value but was able to moderate the effect of sales growth and growth. assets to company value.